Impact of Digital Marketing on Business Performance: A PRISMA Model - Lamichhane, Basudev; Lamichhane, Saujan; Pandey, Prerna; Regmi, Shobhakant (Journal of Development Review, 2025)
This study aims to examine the impacts of digital marketing on business sustainability using a systematic analysis guided by PRISMA, focusing on their effectiveness, emerging trends, and obstacles. By comprehensively examining contemporary academic studies, the research highlights significant digital marketing methods that improve online presence, consumer interaction, and overall business performance. This research is constrained by its dependency on secondary data, which may not adequately reflect current industry trends. Moreover, the study primarily emphasizes existing literature and lacks in empirical data from direct consumer and business surveys. Additionally, variations in the effectiveness of digital marketing across different regions and industries are not thoroughly addressed. The study concludes that transformative trends and technologies are changing the landscape of digital marketing, including artificial intelligence, data driven analytics, and Omni channel marketing strategies positive impact on business sustainability. Further, the study addresses major challenges and concerns about data privacy, content saturation, issues with consumer trust while evaluating return on investment (ROI), reliance on specific platforms, and ethical considerations. The study provides several possible options for the problem that focus more on privacy-related marketing, using AI in personalized content creation, adopting complex analytics for performance assessment, and diversifying marketing channels. The research invariably emphasizes that businesses must infuse their digital marketing efforts with ethics, sound data-unforcedness, and customer focus to attain sustainable growth in their top-tier digital ecosystem. This study offers valuable insights for small and micro-entrepreneurs, policymakers, and regulators emphasizing digital marketing as a tool for sustainable marketing strategies.